Cost-effectiveness of a chronic pain intervention for people living with HIV (PLWH). (1st February 2018) - Merlin, Jessica S.; Westfall, Andrew O.; Johnson, Mallory O.; Kerns, Robert D.; Bair, Matthew J.; Kertesz, Stefan; Turan, Janet M.; Clay, Olivio J.; Starrels, Joanna L.; Kilgore, Meredith
Abstract: Background: Chronic pain is a common, disabling, and costly comorbidity, particularly in people living with HIV (PLWH). This study developed and pilot tested a pain self-management intervention for chronic pain tailored to PLWH called Skills TO Manage Pain (STOMP). Objectives: Given the additional resources needed to deliver STOMP in HIV clinical settings, an important objective of the pilot study was to assess not only STOMP's preliminary efficacy, but also its cost-effectiveness. Research design and subjects: The present study draws from a 44-participant, 2-arm randomized pilot trial of the STOMP intervention vs usual care among PLWH and at least moderate chronic pain (Clinicaltrials.gov: NCT02824562). Cost-effectiveness is presented as the incremental cost-effectiveness ratio (ICER). Costs were considered from the clinic perspective over a 1-year time horizon using real costs from the pilot trial. It was conservatively assumed there would be no costs savings. The Standard Gamble (SG) method was used to directly measure utilities. Results: Thirty-six participants met inclusion criteria for the present analyses. Mean age was 52 years; 61% were female and 86% were black. The total cost of STOMP was $483.83 per person. Using the SG method, the change in QALYs was 0.15, corresponding to an ICER of $3, 225. Conclusions: STOMP's cost/QALY is substantially lower than the $50, 000 to $100, 000/QALY benchmark often used to indicate cost-effectiveness. Although based on a pilot trial and, therefore, preliminary, these findings are promising, and suggest the importance of cost analyses in future STOMP trials.